1996
DOI: 10.1007/s001250050475
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine-induced apoptotic cell death in a mouse pancreatic beta-cell line: inhibition by Bcl-2

Abstract: Cytokines are thought to contribute to the induction of pancreatic beta-cell destruction in insulin-dependent diabetes mellitus. The molecular mechanisms that underlie beta-cell death were investigated by studying cytokine-induced cell death in beta-cell lines. A combination of three cytokines (interleukin-1 beta, tumour necrosis factor-alpha, and interferon-gamma) induced apoptotic cell death in the mouse pancreatic beta-cell line beta TC1, as judged from the appearance of cells with hypodiploid nuclei and ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
4

Year Published

1997
1997
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 0 publications
1
35
0
4
Order By: Relevance
“…The up-regulation by biliverdin/bilirubin of HO-1 would lead to an amplification cycle because more biliverdin is produced by the induced HO-1. In addition to the protective effect of HO-1, up-regulation of bcl-2 in ␤-cells can protect the cells from caspase-mediated cell death, thus contributing to the survival of transplanted islets (32)(33)(34). This is consistent with the suppressed level of caspases in freshly isolated islets and islet grafts at various days after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…The up-regulation by biliverdin/bilirubin of HO-1 would lead to an amplification cycle because more biliverdin is produced by the induced HO-1. In addition to the protective effect of HO-1, up-regulation of bcl-2 in ␤-cells can protect the cells from caspase-mediated cell death, thus contributing to the survival of transplanted islets (32)(33)(34). This is consistent with the suppressed level of caspases in freshly isolated islets and islet grafts at various days after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Addit i o n a l l y, the other transcriptional factors c-j u n and c-f o s, which are also implied in the signaling cascade leading to apoptosis, are induced by IL-1 in rat islets of Langerhans and RINm5F cells (49). In mouse pancreatic -cell lines ( TC1 and N I T-1), the combination of three cytokines (IL-1 , TNF-, and IFN-) was able to induce apoptotic cell death (50). Intere s t i n g l y, this study also showed that overexpression of b c l -2 in TC1 cells partially protected them from cytokine-induced death.…”
Section: A Role For Apoptosis In the Destruction Of -C E L L Smentioning
confidence: 98%
“…When cells sense extracellular molecular cues, such as cytokines, growth factors or stress signals, they react in a wide variety of ways that may change their fate, leading to growth, death or differentiation [1][2][3][4]. Diverse post-translational modifications underlie these changes in cell state [5,6] and the ability to monitor such modifications is essential to make sense of cell physiology and to understand how its perturbation leads to pathological conditions.…”
Section: Introductionmentioning
confidence: 99%